2017
DOI: 10.1016/j.physa.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study on social groups in pedestrian evacuation dynamics

Abstract: Pedestrian crowds often include social groups, i.e. pedestrians that walk together because of social relationships. They show characteristic configurations and influence the dynamics of the entire crowd. In order to investigate the impact of social groups on evacuations we performed an empirical study with pupils. Several evacuation runs with groups of different sizes and different interactions were performed. New group parameters are introduced which allow to describe the dynamics of the groups and the config… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(65 citation statements)
references
References 24 publications
2
62
0
1
Order By: Relevance
“…Research on pedestrian dynamics has systematically analysed the influence of group behaviour only in the last years (see, e.g., [9,2,8]): although observations and experiments agree on some aggregated and microscopic effects of the presence of groups (e.g. group members walk slower than individuals), there is still need for additional insights, for instance on the spatial patterns assumed by groups in their movement and in general on the interaction among different factors influencing overall pedestrian dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Research on pedestrian dynamics has systematically analysed the influence of group behaviour only in the last years (see, e.g., [9,2,8]): although observations and experiments agree on some aggregated and microscopic effects of the presence of groups (e.g. group members walk slower than individuals), there is still need for additional insights, for instance on the spatial patterns assumed by groups in their movement and in general on the interaction among different factors influencing overall pedestrian dynamics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Further, no clear time variation was found between individual and group movements. Similarly, von Krüchten et al (2016) and von Krüchten and Schadschneider (2017) arranged 32-46 participants (dividing into social groups with 4, 6, and 8 people) to egress a narrow door with widths of 0.8m and 1.2m [112,113]. Macroscopic and microscopic features of the egress flows were analyzed.…”
Section: Egress and Ingressmentioning
confidence: 99%
“…It was found that the growing ratio of selfish pedestrians led to the rise and the disorder of flow rate. von Krchten & Schadschneider (2017) investigated the behaviors of social groups and concluded that the increasing size of social groups could have a positive influence on evacuation.…”
Section: Introductionmentioning
confidence: 99%